Development of website usability instrument based on experts review - Aziz, Nur Sukinah; Adzhar, Kamaludin (2015)
Nowadays, website is use widely all over a world for medium of communication for information or services and usability principles was implementing in web environment and not for software only. Organization use website to market their product and services. There are many methods to evaluate the website such as heuristic evaluation, testing, survey and many more. This study is aiming to develop the questionnaire for measure website in context of usability. The instrument consist 9 constructs and 60 item of questionnaire. Content validity by experts is used as one of methodology to validate the instrument. Five experts are involved in this study. The result shows that from 60 item of instrument, 9 item need to remove based on experts review.